Symplectic analysis for the effects of material distribution and relative density on dynamic properties of sandwich tubes with honeycomb cores. Issue 1 (7th March 2016) - Zhang, Kai; Deng, Zichen; Meng, Junmiao; Xu, Xiaojian
Abstract : Purpose: – The purpose of this paper is to provide an efficient numerical solution for dynamic properties of sandwich tubes with honeycomb cores and investigate the effects of material distribution and relative density on the dynamic properties of the structure. Design/methodology/approach: – By introducing dual variables and applying the variational principle, the canonical equations of Hamiltonian system are constructed. The precise integration algorithm and extended Wittrick-Williams algorithm are adopted to solve the equations and obtain the dispersion relations of sandwich tubes. The effects of the material distribution and the relative density on the non-dimensional frequencies of the sandwich tubes are investigated. Findings: – The validity of the procedure and programs is verified by comparing with other works. Dispersion relations of the typical sandwich tubes are obtained. Dramatic differences are observed as the material distribution and relative density of the sandwich structures vary. Originality/value: – The work gains insight into the role of symplectic analysis in the structural dynamic properties and expects to provide new opportunities for the optimal design of sandwich tubes with honeycomb cores in engineering applications.